Sistem Pendukung Keputusan Promosi Jabatan Struktural Dosen Menggunakan AHP (Analytical Hierarchy Process) - Rahma Farah Nungrum (Universitas Muhammadiyah Tangerang, 2017)
Abstrack Good University Governance is needed by all higher education institutions that want to compete in producing good quality colleges. One of them is STT PLN which has a vision of realization of modern universities, independent and superior in the field of energy and electricity. To achieve good management governance, an objective, accountable and transparen,t assessment is required in recommending a lecturer to occupy a structural position. The process of determining attribute criteria, sub criteria and alternatives using the input of expert respondents in the form of questionnaires are processed by using statistical methods Cochran Q Test to obtain the decision attributes used in the study. While the analytical techniques in determining the priority weight of the alternative that will be done, using Analytical Hierarchy Process (AHP) method approach with data processing tool using Expert Choice software. Keywords : Good University Governance, Lecturers, structural positions, Cochran Q Test, Analytical Hierarchy Process (AHP)